Vol. 224 : Ecology and safety in the technosphere: current problems and solutions (EST 2018): All-Russian research-to-practice conference, 22–24 November 2018, Yurga, Russian Federation; IOP Conference Series: Earth and Environmental Science (2019, 2019)
Title screen